High-Throughput Detection of Bacterial Community and Its Drug-Resistance Profiling From Local Reclaimed Wastewater Plants - Alya Limayem; Alya Limayem; Sarah Wasson; Mausam Mehta; Anaya Raj Pokhrel; Shrushti Patil; Minh Nguyen; Minh Nguyen; Jing Chen; Bina Nayak (Frontiers in Cellular and Infection Microbiology, 2019)
Treated wastewater from reclaimed facilities (WWTP) has become a reusable source for a variety of applications, such as agricultural irrigation. However, it is also a potential reservoir of clinically-relevant multidrug resistant (MDR) pathogens, including ESKAPE (Enterococcus faecium and Streptococcus surrogates, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species along with the emerging nosocomial Escherichia strains). This study was performed to decipher the bacterial community structure through Illumina high throughput 16S rRNA gene sequencing, and to determine the resistance profile using the Sensititre antimicrobial susceptibility test (AST) conforming to clinical lab standards (NCCLS). Out of 1747 bacterial strains detected from wastewater influent and effluent, Pseudomonas was the most predominant genus related to ESKAPE in influent, with sequence reads corresponding to 21.356%, followed by Streptococcus (6.445%), Acinetobacter (0.968%), Enterococcus (0.063%), Klebsiella (0.038%), Escherichia (0.028%) and Staphylococcus (0.004%). Despite the different treatment methods used, the effluent still revealed the presence of some Pseudomonas strains (0.066%), and a wide range of gram-positive cocci, including Staphylococcus (0.194%), Streptococcus (0.63%) and Enterococcus (0.037%), in addition to gram-negative Acinetobacter (0.736%), Klebsiella (0.1%), and Escherichia sub-species (0.811%). The AST results indicated that the strains Escherichia along with Klebsiella and Acinetobacter, isolated from the effluent, displayed resistance to 11 antibiotics, while Pseudomonas was resistant to 7 antibiotics, and Streptococcus along with Staphylococcus were resistant to 9 antibiotics. Results herein, proved the existence of some nosocomial MDR pathogens, known for ESKAPE, with potential drug resistance transfer to the non-pathogen microbes, requiring targeted remediation.